Pengaruh Kompetensi, Pelatihan Dan Stres Kerja Terhadap Kinerja Karyawan Pada PT Eka Paksi Sejati - Kristi Endah Ndilosa Ginting; Tommy Dharmawan Liem; Fernando Chiuman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
In a system can run and operate well and good if there is a regulation that really involves human resources. At PT Eka Paksi Sejati this decline in employee performance can be seen from the failure to achieve sales targets and sales realization. Competence is one of the important factors in a company, but at PT Eka Paksi Sejati there are competency problems caused by employee work placements and employee competencies that are not appropriate. There are many employees whose educational backgrounds and positions do not match, causing problems in the employee's work. Job training is also very important for companies because employees can master and be able to overcome their problems in doing their jobs. And employees can be happy to accept their work even though the educational background is different from the work. Low work discipline at PT Eka Paksi Sejati can occur due to a lack of employee understanding of the existing regulations, giving rise to different perceptions which can also lead to a lack of employee awareness to comply with the applicable regulations in the company, a lack of sense of responsibility towards work. This study aims to determine the effect of competence, training and work discipline on employee performance at PT Eka Paksi Sejati. The data used in this study is primary data obtained by distributing questionnaires to all employees of the company and the results of this test prove that competence (X1), training (X2) and work stress (X3) have a significant simultaneous effect on employee performance. Keywords : Competence, Training, Job Stress, Performance